Functional assessment of the liver with gadolinium–ethoxybenzyl‐diethylenetriamine penta‐acetate‐enhanced MRI in living‐donor liver transplantation. Issue 8 (29th April 2015) - Ninomiya, M.; Shirabe, K.; Kayashima, H.; Ikegami, T.; Nishie, A.; Harimoto, N.; Yamashita, Y.; Yoshizumi, T.; Uchiyama, H.; Maehara, Y.
<x xml:space="preserve">Abstract</x> Background A precise estimation of the capacity of the remnant liver following partial liver resection is important. In this study, the regional function of the liver in patients undergoing living‐donor liver transplantation was evaluated by gadolinium–ethoxybenzyl‐diethylenetriamine penta‐acetic acid (EOB)‐enhanced MRI, with special reference to the congested region. Methods EOB‐MRI analysis was performed before hepatectomy in donors, and 7 days after surgery in the donor and recipient. In the hepatocyte phase, from images obtained 15 min after Primovist® injection, the signal intensity in each liver segment was measured and divided by the signal intensity of the erector spinae muscle (liver to muscle ratio, LMR) for standardization. Inter‐regional differences in LMRs were analysed in donors and recipients. Results Thirty‐two living donors and 31 recipients undergoing living‐donor liver transplantation were enrolled. In donors, the LMRs of the remnant left lobe were almost equivalent among the liver segments. In the remnant right lobe without the middle hepatic vein, the mean(s.d.) LMR for congested segments (S5 and S8) was significantly lower than that for non‐congested segments (S6 and S7): 2·60(0·52) versus 3·64(0·56) respectively (P < 0·001). After surgery, values in the non‐congested region were almost identical to those in the preoperative donor liver. LMR values in the left and right lobe graft were significantly lower than those in the corresponding segment before donor surgery (P < 0·001). Conclusion The function of the congested region secondary to outflow obstruction in the remnant donor liver was approximately 70 per cent of that in the non‐congested region. EOB‐MRI is a promising tool to assess regional liver function, with good spatial resolution.